Informasi Akuntansi Pertanggungjawaban Sebagai Alat Penilaian Kinerja Manajer Perusahaan Asuransi Jiwa Bersama Bumi Putera Kota Batu - Putri Anggraini; Dwiyani Sudaryanti; Siti Aminah Anwar (Universitas Islam Malang, 2023)
Accounting information is the final result of the responsibility center where later the information can be used to evaluate the performance of each company unit. Accountability accounting is needed by company managers as a benchmark for the performance of each unit. The existence of corporate responsibility accounting can be controlled and directed according to targets and objectives. The responsibility accounting report becomes an assessment of the performance of a company in one period. The company insurance of Bumi Putera Batu is one of the companies that has a responsibility center unit. Where this responsibility center will report accounting information on the performance that has been done in a certain period to the company manager. The use of code in accounts has also been applied in liability accounting. The insurance company Bumi Putera has implemented an accounting system in the company's operations. The company in its application has used a fairly good accounting system.Keyword: Accounting Information, Company Manager Performance, Code Usage in Accounting Information